Flavonolignans silybin, silychristin and 2,3-dehydrosilybin showed differential cytoprotective, antioxidant and anti-apoptotic effects on splenocytes from Balb/c mice - Jurčacková, Zuzana; Hrčková, Gabriela; Mudroňová, Dagmar; Matiašová, Anna Alexovič; Biedermann, David (Scientific reports, 2025)
Silymarin is an extract obtained from the seeds of milk thistle (Sylibum marianum L., Asteraceae) and contains several structurally related flavonolignans and a small family of flavonoids. Mouse spleen cells represent highly sensitive primary cells suitable for studying the pharmacological potential and biofunctional properties of natural substances. Cultivation of splenocytes for 24 h under standard culture conditions (humidity, 37 °C, 5% CO2, atmospheric oxygen) resulted in decreased viability of splenocytes compared to intact cells. A cytoprotective effect of silybin (SB), silychristin (SCH) and 2,3-dehydrosilybin (DHSB) was observed at concentrations as low as 5 µmol/ml. At 50 µmol/ml, these substances restored and/or stimulated viability and mitochondrial membrane potential and had anti-apoptotic effect in the order SB > DHSB > SCH. The substances demonstrated a concentration-dependent activity in restoring the redox balance based on the changes in the concentration of reactive oxygen species (ROS), hydrogen peroxide (H2O2) and nitric oxide. This was in the order DHSB > SCH > SB, which correlated with the suppressed expression of nuclear factor erythroid 2-related factor 2 (Nrf2), catalase and glutathione peroxidase. The strong stimulation of the superoxide dismutase 1 gene converting ROS to H2O2 points to its dominant role in the maintaining redox homeostasis in splenocytes, which was disrupted by oxidative stress due to non-physiological culture conditions. Our study showed significant differences in the cytoprotective, antioxidant and anti-apoptotic activities of SB, SCH, and DHSB on splenocytes exposed to mild and AAPH-induced oxidative stress.
Keywords: Silychristin; Mice, Inbred BALB C; apoptóza; Antioxidants; NF-E2-Related Factor 2; reaktivní formy kyslíku; Silybin; Redox balance; silymarin; peroxid vodíku; Oxidative Stress; Mice; Mouse splenocytes; membránový potenciál mitochondrií; Silymarin; slezina; antioxidancia; Reactive Oxygen Species; silibinin; zvířata; oxid dusnatý; Nitric Oxide; 2,3-dehydrosilybin; myši inbrední BALB C; faktor 2 související s NF-E2; viabilita buněk; Cell Survival; Viability; myši; Cytoprotection; Membrane Potential, Mitochondrial; oxidační stres; Spleen; cytoprotekce; Hydrogen Peroxide; Apoptosis; Animals